The Impact of Capital Market on Industrial Growth in Nigeria: Does Islamic Capital Market an Alternative? - Gani, Ibrahim Musa (Economics & Islamic Finance Journal (ECIF), 2025)
Over the years, capital markets have played a pivotal role in channelling funds towards the industrial sector, thus influencing the Nigeria’s industrial and economic progress. This study explores the intricate relationship between capital market and industrial growth and development in Nigeria, and whether the Islamic capital market can be the alternative in increasing the value of transactions in government and industrial securities to enhance industrial development in Nigeria. The study employs a comprehensive research framework that encompasses Johansen and Johansen (JJ) co-integration regression analyses. The findings of this research underscore the significance of capital markets as a critical driver of industrial growth in Nigeria. The capital raised through these markets has contributed to expanding existing industries and establishing new ones. It has facilitated technological advancements, improved infrastructure, and enhanced the competitiveness of Nigerian industries on the global stage. In conclusion, this research explodes the pivotal role of capital markets in shaping the industrial landscape of Nigeria. By understanding and addressing the challenges, policymakers, and stakeholders can harness the full potential of capital markets to drive sustainable industrial growth and development, ultimately contributing to the broader economic prosperity of the nation. Moreover, structuring and strengthening the non interest Islamic capital market is paramount, this is in order to avoid exorbitant interest rate charged in the structure of financial market instruments and served as alternative to conventional capital market. Islamic capital market provides an alternative capital as well as varieties of financial instruments that may be productive to industrial sector such as Sukuk, among others. These financial assets are capable of minimising cost of borrowing, as the product of Islamic capital market are not giving fund directly as loan of capital, in this case Islamic capital market would finance the earmarked industrial projects till completed (like Bay Salam).